1999
DOI: 10.1099/00207713-49-3-1015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraspecies genetic variation within the 60 kDa heat-shock protein gene (groEL) of Bartonella species

Abstract: A phylogenetic investigation was done on the members of the genus Battonella, based on the DNA sequence analysis of the groEf gene, which encodes the 60 kDa heat-shock protein GroEL. Nucleotide sequence data were determined for a near full-length fragment (1368 bp) of the gm€L gene of the established Bartonella species and used to infer intraspecies phylogenetic relationships. Phylogenetic trees were inferred from multiple sequence alignments by using both distance and parsimony methods, which demonstrated an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 55 publications
(40 reference statements)
1
63
0
2
Order By: Relevance
“…The results showed that the similarity of nucleotide sequences were very high (greater than 99% identity) in this 590-bp region, and the deduced amino acid sequences from three isolates were identical to that of ATCC 29212 and one is identical to that of ATCC 19434. Intraspecies variation of groEL among Bartonella and Ehrlichia species has been studied by Marston et al and Sumner et al, respectively, and their reports revealed that some sequence divergence may be evident between strains from different countries (17,26).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the similarity of nucleotide sequences were very high (greater than 99% identity) in this 590-bp region, and the deduced amino acid sequences from three isolates were identical to that of ATCC 29212 and one is identical to that of ATCC 19434. Intraspecies variation of groEL among Bartonella and Ehrlichia species has been studied by Marston et al and Sumner et al, respectively, and their reports revealed that some sequence divergence may be evident between strains from different countries (17,26).…”
Section: Discussionmentioning
confidence: 99%
“…GroEL is the highly coserved heat shock chaperonin system of proteins in bacteria providing a phylogenetic relationship to bacteria (4,11). The groEL gene provides better topological and statistical support than gltA and 16S rRNA within Bartonella species (11).…”
Section: Ovis)mentioning
confidence: 99%
“…The groEL gene provides better topological and statistical support than gltA and 16S rRNA within Bartonella species (11). Two set primers were designed and synthesized for highly sensitive nested PCR.…”
Section: Ovis)mentioning
confidence: 99%
“…The highly conserved 60 kDa heat-shock protein (HSP60) has been considered to be another useful phylogenetic marker and sequence comparisons of its gene have been used for species identification and phylogenetic analysis of the genera Staphylococcus (Kwok et al, 1999) and Bartonella (Marston et al, 1999). In our previous work (Jian et al, 2001), it was indicated that the HSP60 gene may also be a useful tool for phylogenetic study of the genus Bifidobacterium.…”
mentioning
confidence: 99%